Public trust in Islamic banking products and services in a post-conflict and post-disaster transitional region: a case study of Bank Aceh Syariah, Bireuen branch - Chairul Bariah; Dayan Abdurrahman (Institute of Computer Science (IOCS), 2026)
Public trust is the foundation of financial stability, yet little is known about how trust in Islamic banking forms in regions recovering from conflict and disaster. Most research focuses on stable settings, rarely combining institutional resilience, crisis response, and Shariah values in one framework. This study addresses this gap by examining trust drivers at Bank Aceh Syariah Bireuen Branch—an area emerging from 30 years of conflict and still prone to natural hazards. Drawing on Signaling Theory, Social Exchange Theory, and Maq??id al-Shar??ah, it tests how Shariah compliance, service quality, governance, digital banking, and post-crisis responsiveness shape trust. Data from 320 customers were analyzed via PLS-SEM. Shariah compliance (? = 0.312, p < 0.001), service quality (? = 0.278, p < 0.01), and post-crisis responsiveness (? = 0.245, p < 0.01) are the strongest predictors; governance and digital quality also have positive effects. Uniquely, this work integrates post-disaster responsiveness into Islamic banking trust research. It advances trust theory for fragile contexts and provides actionable guidance for banks and regulators building resilience and inclusion in post-crisis regions.